Role of Host-Guest Interaction in Understanding Polymerisation in Metal-Organic Frameworks - Wonanke, A.D. Dinga; Bennett, Poppy; Caldwell, Lewis; Addicoat, Matthew A. (Frontiers in Chemistry, 2021)
Metal-organic frameworks, MOFs, offer an effective template for polymerisation of polymers with precisely controlled structures within the sub-nanometre scales. However, synthetic difficulties such as monomer infiltration, detailed understanding of polymerisation mechanisms within the MOF nanochannels and the mechanism for removing the MOF template post polymerisation have prevented wide scale implementation of polymerisation in MOFs. This is partly due to the significant lack in understanding of the energetic and atomic-scale intermolecular interactions between the monomers and the MOFs. Consequently in this study, we explore the interaction of varied concentration of styrene, and EDOT, at the surface and in the nanochannel of Zn2(1,4-ndc)2(dabco), where 1,4-ndc = 1,4-naphthalenedicarboxylate and dabco = 1,4-diazabicyclo[2.2.2]octane. Our results showed that the interactions between monomers are stronger in the nanochannels than at the surfaces of the MOF. Moreover, the MOF-monomer interactions are strongest in the nanochannels and increase with the number of monomers. However, as the number of monomers increases, the monomers turn to bind more strongly at the surface leading to a potential agglomeration of the monomers at the surface.